Perambahan Hutan Taman Nasional Kerinci Seblat (TNKS) dan Upaya Penanggulangannya dalam Perspektif Hukum Islam dan Hukum Positif - Adawiyah, Robi'atul; Putra, Devrian Ali; Hadi, Syamsu; Alfian, Elvi; Sukmawati, Nilam; Subhan, Subhan (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
The problem raised in this study was the law enforcement against actors encroaching on TNKS forests. This study was to know the role of law enforcement officials and the law enforcement process against actors of TNKS forest encroachment, obstacles experienced by law enforcement officers. The research method uses a juridical-empirical research approach with qualitative data analysis. Based on the results of the research, the following conclusions: First, the cause of encroachment of the TNKS forest in Jangkat sub-district is due to economic factors, educational and factors of the number of law enforcement officers. Second, the role of law enforcement officers and the community in law enforcement which includes roles in preventive and repressive. Third, efforts that must be made to prevent and eradicate forest encroachment in Jangkat District are: (1). Improve the legal substance; (2). Improve supporting facilities; (3). Increase patrols; (4). Give more understanding to the community about the importance of protecting the forest.